2000
DOI: 10.1103/physrevb.61.r11859
|View full text |Cite
|
Sign up to set email alerts
|

Critical statistics in a power-law random-banded matrix ensemble

Abstract: We investigate the statistical properties of the eigenvalues and eigenvectors in a random matrix ensemble with Hij ∼ |i − j| −µ . It is known that this model shows a localization-delocalization transition (LDT) as a function of the parameter µ. The model is critical at µ = 1 and the eigenstates are multifractals. Based on numerical simulations we demonstrate that the spectral statistics at criticality differs from semi-Poisson statistics which is expected to be a general feature of systems exhibiting a LDT or … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 29 publications
4
59
0
Order By: Relevance
“…In order to fully represent the mesoscopic systems we introduce an explicit dependence on dimensionality d in the widely studied power-law random banded matrix (PRBM) ensemble [5,7,9,11,[26][27][28][29][30][31][32][33][34][35][36] (for closely related models see also Ref. [37]).…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to fully represent the mesoscopic systems we introduce an explicit dependence on dimensionality d in the widely studied power-law random banded matrix (PRBM) ensemble [5,7,9,11,[26][27][28][29][30][31][32][33][34][35][36] (for closely related models see also Ref. [37]).…”
Section: The Modelmentioning
confidence: 99%
“…Although a great progress in understanding critical properties of the 1d long-range random hopping Hamiltonian has recently been made [5,7,9,11,[26][27][28][29][30][31][32][33][34][35][36][37] explicit results for the 2d and 3d systems are still lacking. Our aim was to investigate the two previously mentioned important quantities, the correlation dimension and nearest level spacing distribution, at the MIT, which have been left unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…At the critical value α = 1, we expect to have multifractal eigenstates and critical level statistics, intermediate between Poisson and Wigner-Dyson. Recent numerical calculations at criticality and for b = 1 have shown that the nearest level spacing distribution differs from the typical one at a metal-insulator transition [15].…”
mentioning
confidence: 96%
“…At the critical value α = 1, we expect to have multifractal eigenstates and critical level statistics, intermediate between Poisson and Wigner-Dyson. Recent numerical calculations at criticality and for b = 1 have shown that the nearest level spacing distribution differs from the typical one at a metal-insulator transition [15].Our aim in this paper is to explore in detail the characteristics of the PRBM model in the interesting regime around α ≈ 1 and for the case b = 1 where theoretical treatments are not strictly applicable. We do so by studying systematically the nearest level spacing distribution function P (s), the behavior of the Green function (GF) as a function of distance and the fractal properties of the states.…”
mentioning
confidence: 99%
“…Ref. 17 ) typical for the spectra of matrices from the Gaussian orthogonal ensemble, which do not show any change in the level-spacing statistics (the Wigner surmise) across the band 18 . The inset in Fig.…”
Section: It Is Knownmentioning
confidence: 99%